Pengaruh Media Sosial terhadap Motivasi Belajar Siswa pada Mata Pelajaran Geografi Fase E SMAN 1 Kecamatan Guguak Kabupaten 50 Kota - Salamah, Ummi; Chandra, Deded (Lembaga Yasin AlSys, 2024)
This study is to investigate the impact of social media on students' motivation to learn Geography in phase E at SMAN 1, Guguak District, 50 City District, during the academic year 2023/2024. The research methodology employed in this study is experimental research, as its objective is to investigate the impact of variable X on variable Y. The population under study comprises all students in class X. The sample size for the study is 59 respondents. The research was conducted at SMA Negeri 1 Guguak, situated on Jl. Tan Malaka Kubang Tungkek, Guguak District, Limapuluh Kota Regency. The research will be conducted in SMA N 1 Guguak sub-district. Meanwhile, the research will be carried out in May 2024. The research findings indicate that social media has an impact on the motivation of students in phase E geography topics at SMAN 1, Guguak District, 50 City District. Evidently, the research findings indicate that the students in the experimental class, where social media was employed as a learning tool, had greater ratings in the category of learning motivation compared to the control class, which relied on traditional methods such as lectures. In addition, the examination of pretest, posttest, and questionnaire scores reveals that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. Thus, the hypothesis posits that social media has an impact on students' drive to learn.